A survey of the General Assembly's competence in matters of international peace and security: in law and practice. (2nd January 2021) - Barber, Rebecca
ABSTRACT: This article examines the General Assembly's history of engagement in international peace and security, and assesses the relevance of that practice to the determination of its legal competence. It first discusses the Assembly's legal competence in international peace and security as described by the UN Charter, and then provides a catalogue of precedent to illustrate that the way in which the Assembly has engaged in such matters supports the widest possible interpretation of its powers. It surveys the Assembly's engagement in four categories of cases: foreign aggression; self-determination; apartheid; and civil conflict. For each, it considers the action taken by the Security Council, how the matters came before the Assembly, and what grounds were cited for the Assembly's interventions. It then considers the nature of the Assembly's responses, including the establishment of peacekeeping forces, recommendations regarding sanctions and the use of military force, and recommendations made to the Security Council.